Sistem Informasi Pelayanan Masyarakat Kelurahan Pasar Kliwon – Surakarta dengan PHP dan MySQL - Ginting, Taman; Graha Nur Pradoni, Lingga; Warasto, Didik; Jalil, Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2023)
Pasar Kliwon Village is a village located in Surakarta city, Pasar Kliwon village is bordered from the north by Kedung Lumbu Village, to the south by Joyosuran Village, to the west by Gajahan Village and Pasar Kliwon Village, to the east by Semanggi Village and Mojo Village. This village is located at Mijil Street No. 6 Gurawan Pasar Kliwon , Pasar Kliwon District, Surakarta City. D3 Pratama Mulia Surakarta Polytechnic Program, Informatics Management. The purpose of this final project is to create a website for Information on Types and Requirements for Community Service in Pasar Kliwon Village. The website that was created aims to make it easier for people to not go back and forth when looking for population administration and accelerate the performance of admins in helping the information processing process quickly, precisely and accurately. This website system is made with PHP program and MySQL database. It can be concluded that this system is ready to be developed.